Phylogeny of Plant Calcium and Calmodulin-Dependent Protein Kinases (CCaMKs) and Functional Analyses of Tomato CCaMK in Disease Resistance - Wang, Ji-Peng; Munyampundu, Jean-Pierre; Xu, You-Ping; Cai, Xin-Zhong (Frontiers in Plant Science, 2015)
Calcium and calmodulin-dependent protein kinase (CCaMK) is a member of calcium/calmodulin-dependent protein kinase superfamily and is essential to microbe- plant symbiosis. To date, the distribution of CCaMK gene in plants has not yet been completely understood, and its function in plant disease resistance remains unclear. In this study, we systemically identified the CCaMK genes in genomes of 44 plant species in Phytozome and analyzed the function of tomato CCaMK (SlCCaMK) in resistance to various pathogens. CCaMKs in 18 additional plant species were identified, yet the absence of CCaMK gene in green algae and cruciferous species was confirmed. Sequence analysis of full-length CCaMK proteins from 44 plant species demonstrated that plant CCaMKs are highly conserved across all domains. Most of the important regulatory amino acids are conserved throughout all sequences, with the only notable exception being observed in N-terminal autophosphorylation site corresponding to Ser 9 in the Medicago truncatula CCaMK. CCaMK gene structures are similar, mostly containing six introns with a phase profile of 200200 and the exception was only noticed at the first exons. Phylogenetic analysis demonstrated that CCaMK lineage is likely to have diverged early from a calcium-dependent protein kinase (CDPK) gene in the ancestor of all nonvascular plant species. The SlCCaMK gene was widely and differently responsive to diverse pathogenic stimuli. Furthermore, knock-down of SlCCaMK reduced tomato resistance to Sclerotinia sclerotiorum and Pseudomonas syringae pv. tomato (Pst) DC3000 and decreased H2O2 accumulation in response to Pst DC3000 inoculation. Our results reveal that SlCCaMK positively regulates disease resistance in tomato via promoting H2O2 accumulation. SlCCaMK is the first CCaMK gene proved to function in plant disease resistance.